Stipa baktashevae, a new synonym of Stipa borysthenica (Poaceae) - Nobis, Marcin; Klichowska, Ewelina (Phytotaxa, 2016)
Numerical analyses of macromorphological characters of specimens of S. lessingiana, S. borysthenica and S. baktashevae, nested the last one among individuals of S. borysthenica. We propose synonymization of S. baktashevae, the species described in 2014 and known only from type material, with S. borysthenica, and provide morphological comparisons of the taxa.